2014
DOI: 10.1007/s12155-014-9529-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Soil Organic Carbon Changes Under Different Maize Cropping Scenarios for Cellulosic Ethanol in Europe

Abstract: The utilization of crop residues in the production of second-generation biofuels has the potential to boost the bioenergy sector without affecting food commodity prices. However, policies leading to large-scale biomass removal should carefully balance the consequences, both environmental and in terms of emissions, on soil organic carbon (SOC) stocks depletion. Using a recently developed simulation platform, SOC changes were estimated at European level (EU + candidate and potential candidate countries) under tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To preserve soil quality and system productivity, quantitative and qualitative attributes of stover along with other information (e.g. soil type, soil management system, climate) is required to carefully establish proper harvest levels (Blanco-Canqui, 2013;Lugato;Jones, 2015). It is worth noting that since hybrids are the cultivars most widely used in grain production systems (Cruz;Pereira, 2008), the removal and use of their stover is more likely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To preserve soil quality and system productivity, quantitative and qualitative attributes of stover along with other information (e.g. soil type, soil management system, climate) is required to carefully establish proper harvest levels (Blanco-Canqui, 2013;Lugato;Jones, 2015). It is worth noting that since hybrids are the cultivars most widely used in grain production systems (Cruz;Pereira, 2008), the removal and use of their stover is more likely.…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of cropping systems with no soil tillage has been effective in increasing SOM levels due to a reduction in the loss of C by not turning over the soil (Kumar et al, 2012;Corbeels et al, 2016). In this sense, the intensification of crop rotations using crops with high stover addition (e.g., corn) contributes to positive soil C balance (Govaerts et al, 2009;Lugato;Jones, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies considers valueadded coproducts derived from HLFB (Schutyser et al 2018, Liu et al 2019. Return of HLFB to the soil has been considered at a conceptual level (Johnson et al 2004, 2007, Johnson 2019 and in a few simulation studies (Pourhashem et al 2013, Adler et al 2015, Lugato and Jones 2015, but lab data are too scant to be conclusive and to our knowledge field studies examining HLFB return have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Stover removal can also reduce returns of organic matter and plant nutrients to the soil. In a simulation study, Lugato and Jones (2015) estimated that for every metric tonne (Mg) of crop residue that is removed from fields in Europe, the soil organic carbon (SOC) losses would be between 0.2 and 0.5 Mg CO 2 eq ha −1 yr −1 . However, only a few studies have examined the overall effect of this practice on soil biological communities (Lehman et al, 2014;Urra, Mijangos, Lanzén, Lloveras, & Garbisu, 2018), with no studies in the humid regions of eastern Canada.…”
Section: Introductionmentioning
confidence: 99%